Water volume by digital image processing of public reservoir in Sume, Paraiba, Brazil - Santos, Maria Paloma Alves dos; Sousa, José Hugo Simplicio de; Nascimento, Abdalan Andrade do; Ribeiro, George do Nascimento; Prado Júnior, Leonardo Souza do; Oliveira Neto, Jose Nunes de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The referred research highlights the importance of water, emphasizing the knowledge of the amount of volume in storage, as an indispensable proposition, especially in regions where there are irregularities in the amount of rain and in the distribution over time. Remote sensing has been gaining a lot of space in management of the basins, as it helps to identify and monitor possible changes in natural resources. The Sumé public reservoir is located in the hydrographic basin of the Alto Rio Paraiba, in the cariri region of Paraiba, with a maximum storage capacity of 44.8 million m3 with a relative area of the water mirror of 8.5 million m2, to carry out this research, orbital images from the Landsat 8/OLI, Landsat 5/TM and ETM and Landsat 7/TM and ETM+ satellites were used. the system used for digital processing was SPRING version 5.5.1. For digital image processing, the following methodologies were used: contrast; main components (bands 5, 4 and 3 - Landsat 5 and 7; and 6, 5 and 4 - Landsat 8); IVDN; highlight by decorrelation (DECO); adjusted multispectral composition (CMA); and, false color composition. The RGB-CONTRASTE was the one with the highest correlation (0.9998), accompanied by CMA-DECO with (0.9979). Remote sensing proved to be effective for the study of water resources, being an economically viable method with fast results.